Identification and characterization of photo-thermo insensitive cowpea (Vigna unguiculata) genotypes for hot arid environment - AJAY KUMAR VERMA; D K SAMADIA; HANUMAN RAM; CHET RAM; GANGADHARA K; P S GURJAR (The Indian Journal of Agricultural Sciences, 2023)
High green pod yield, dual purpose type, earliness and photo-thermo insensitivity are the major breeding objectives of cowpea [Vigna unguiculata (L.) Walp.]. Photo-thermo sensitivity makes this crop vulnerable to photoperiod and temperature fluctuations particularly in hot arid regions, thereby affecting its yield potential drastically. Therefore, the present study was aimed to identify such elite genotypes with photo-thermo insensitivity, which can fit well across all seasons under hot arid environment. The experiments were conducted at ICAR-Central Institute for Arid Horticulture, Bikaner during rainy and summer seasons of 2019–20 and 2020–21. A wide range of variability among genotypes was observed with respect to various phenological and yield traits over the environments. Among the evaluated genotypes, AHCP-1-4-1 and AHCP-2-3 were found photo-thermo insensitive as these were able to flower and set pods at temperatures as low as 10oC and as high as 46°C. Pollen viability studies indicated that AHCP-1-4-1 had 83.72 and 88.24% pollen viability and AHCP-2-3 had 81.58 and 85.71% viable pollen at 11°C and 46°C, respectively and normal pollen tube growth at both the extremes of temperature. The identified genetic resources will contribute for developing photo-thermo insensitive cultivars and will improve the productivity and extend the availability of cowpea with quality pod yield across all seasons and locations of hot arid regions.